EFISIENSI PENGGUNAAN KOLAM TERPAL SEBAGAI MEDIA PEMBESARAN NILA LARASATI (OREOCHROMIS NILOTICUS) PADA LAHAN PERKEBUNAN - Negara, I.K.W.; Hendrawan, I.G.; Dirgayusa, I.G.N.P.; Indrawan, G.S. (Buletin Udayana Mengabdi, 2023)
Larasati tilapia (Oreochromis niloticus) can digest food efficiently, has fast growth, and is more resistant to disease, broad adaptability, and high tolerance to various environmental conditions so that it is prospectively cultivated in flowing water ponds (circulation). Galungan Village has the potential of Aquatic Resources that can be utilized for cultivation activities for Larasati tilapia enlargement. This service is carried out in several stages, namely; the location survey stage for pond construction, seed preparation, outreach, and evaluation. The purpose of this service is to be able to create an efficient Larasati tilapia cultivation medium to maximize the potential of aquatic resources in Galungan Village. This activity starts from the process of making tarpaulin ponds which is an implementation of research, carried out by the Mina Asih Sejati Fish Farmers Group (Pokdakan). The result of this activity is that the tarpaulin pond has no leaks or damage after the process of filling the water for 2 days so the pond is suitable for spreading Larasati tilapia seeds. The next activities were seed distribution and delivery of larasati tilapia feed to Pokdakan as well as mentoring and counseling carried out by the Buleleng Regency Fisheries and Resilience Service. The conclusion from this activity is that the use of tarpaulin ponds as a cultivation medium can achieve maximum goals without having to damage the main crops on the plantation by minimizing costs to produce the maximum pond area. Keywords: Aquaculture, Larasati Tilapia (Oreochromis niloticus), Tarpaulin Pond, Galungan Village